2012
DOI: 10.5539/ibr.v5n11p54
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Decentralization and Employment in Pakistan

Abstract: Study emphasis that a successful fiscal decentralization process is a way to increase the participation of citizens in local level development and economic activities. Study explores that the fiscal decentralization has positive effect on employment generation while the negative relation with inflation and indirectly supports the positive relation with economic growth. Improvement in educational activities and economic integration promote employment activities in the state and fiscally decentralized economy ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
6
4
0
3
Order By: Relevance
“…Research from Sinaga, et al (2005) in Indonesia found a positive effect of profitsharing funds on employment performance. This result is in line with findings from Faridi, et al (2012) which reveals the positive effect of fiscal decentralization by employment in its study in Pakistan. Then Pujiati (2010) proves the positive influence of profit-sharing funds on economic growth and employment.…”
Section: Revenue Sharing Of Natural Resource On Labor Growthsupporting
confidence: 91%
“…Research from Sinaga, et al (2005) in Indonesia found a positive effect of profitsharing funds on employment performance. This result is in line with findings from Faridi, et al (2012) which reveals the positive effect of fiscal decentralization by employment in its study in Pakistan. Then Pujiati (2010) proves the positive influence of profit-sharing funds on economic growth and employment.…”
Section: Revenue Sharing Of Natural Resource On Labor Growthsupporting
confidence: 91%
“…This balancing fund acts as the main source of capital accumulation that encourages increased economic activity in the region. The results of research related to indicators of income decentralization which have a positive coefficient are the same as the results of research conducted by Akai and Sakata (2002), Wibowo (2008), Faridi (2011), Khamdana (2016. Based on the estimation results of the balancing fund ratio variable, it can answer hypothesis I, namely H0 is rejected and H1 is accepted; the ratio of balance funds has a positive and significant effect on the regional economic growth of the Nias Islands.…”
Section: Source: Research Analysis Resultssupporting
confidence: 64%
“…It should also be noted that even when the same estimating techniques and variables are used, the results might vary due to time zone differences. As cited in Faridi (2011) constructed research on the impact of fiscal decentralization on economic expansion. The fiscal decentralization is the process through which local or provincial governments are given control or delegation of power over the economic operations within a province or state.…”
Section: Literature Reviewmentioning
confidence: 99%